EVALUATION OF MINIMUM NUTRITION SERVICE STANDART AT NUTRITION INSTALLATION OF DR. HARJONO PONOROGOGENERAL HOSPITAL - Windatari, Larastiti (Jurnal Gizi dan Kesehatan Nusantara, 2024)
Hospital nutrition services aim to improve health services for all patients with optimal food services according to standards. This study aims to determine the achievement of timeliness, dietary accuracy, and food waste. This study is a quantitative descriptive study with Dr. Harjono Ponorogo Hospital as the subject and minimum service standards as the object given to 300 respondents with the criteria of receiving a regular diet and aged 17-65 years. Data was collected through observation sheets or forms to record the timeliness of feeding, diet accuracy, and food waste by applying the Comstock visual method. Based on the study's results, the average age of respondents was late elderly (55-65 years), with 107 respondents (35.7%). The characteristics of respondents consisted of 156 men (52%) and 144 women (48%). The conclusion of this research is that the achievement of timeliness and diet reached 100%, but food waste was 25.12% and did not meet the minimum standards of Ministry of Health Number 129 of 2008, which is ≤20%.